1996
DOI: 10.1093/jnci/88.19.1399
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Growth and Tumor Radiosensitivity in Mice Given Myeloprotective Doses of Fibroblast Growth Factors

Abstract: Low intravenous doses of FGF1 or FGF2 appear to protect bone marrow from the toxic effects of radiation without increasing the rates of tumor growth or metastases or decreasing the radiosensitivity of tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…However, no studies to date have provided any evidence of malignant transformation resulting from the use of supplemental growth factors when no preexisting genetic mutation exists. When tumors were implanted in mice given supplemental bFGF, no statistical increase in tumor growth rates was seen 49 . Furthermore, no clinical study has shown increased propensity to keloid or hypertrophic scar formation with growth factor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies to date have provided any evidence of malignant transformation resulting from the use of supplemental growth factors when no preexisting genetic mutation exists. When tumors were implanted in mice given supplemental bFGF, no statistical increase in tumor growth rates was seen 49 . Furthermore, no clinical study has shown increased propensity to keloid or hypertrophic scar formation with growth factor therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies, the authors and others have found that FGF-P and FGF-2 mitigate radiation-induced damage to the bone marrow, small bowel, and skin and can improve the bone growth of irradiated juvenile murine femurs (Okunieff et al 1995(Okunieff et al , 1999(Okunieff et al , 2001(Okunieff et al , 2007Ding et al 1996Ding et al , 1997Ding et al , 2002Ding et al , 2003Wang et al 1998;Zhang et al 2010Zhang et al , 2011Budiraharjo et al 2013;Ma et al 2013;Shi et al 2013). Randomized studies in humans using bovine FGF-2 have demonstrated improved healing of ischemic wounds for patients with diabetes and burns at graft and donor sites (Fu et al 1998(Fu et al , 2000.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies demonstrate that FGFs given in almost any schedule beginning 48 h before irradiation to 24 h after irradiation, can reduce haematopoietic toxicity, 19,[21][22][23][24][25][26] small bowel crypt stem cell loss, 14,15 pulmonary radiosensitivity, 16,17,31,32 and bone growth defects after irradiation. 5,18,33 Other FGF isoforms can also radioprotect in a variety of circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The time periods before and after completion of TBI were chosen based on pre-clinical data demonstrating a radioprotective effect of bFGF during those periods. 19,[21][22][23][24][25][26] Daily blood samples collected during the week following the reinfusion of marrow suggest that marrow reinfusion has no significant effect on plasma bFGF concentrations. After collection in EDTA, plasma was briefly stored on ice, centrifuged at 3000 g for 30 min and aliquoted for later analysis.…”
Section: Methodsmentioning
confidence: 99%